Effect of Distributive Justice on The Relationship between The Forms of Benefit Program and Job Commitment - Azman Ismail; Chong Siaw Joon (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
This study was conducted to examine the moderating effect of distributive justice in the relationship between the forms of benefits program and job commitment. A survey research method was used to gather 150 usable questionnaires from employees who have worked in Malaysian federal government linked companies in Sarawak (MFGLS). The outcomes of testing moderating model using a hierarchical regression analysis showed two major findings: (1) distributive justice had not increased the effect of physical and safety benefits (i.e., health care, insurance, loan and claim) on job commitment, and (2) distributive justice had increased the effect of self-satisfaction benefits (i.e., promotion opportunity and training) on job commitment. This result confirms that distributive justice does act as a partial moderating variable in the benefit program models of the organizational sector sample. In addition, the implications of this study to benefit system theory and practice, methodological and conceptual limitations, and directions for future research are also discussed. Keywords: Forms of Benefits Program, Distributive Justice and Job Commitment